2020
DOI: 10.1007/s00394-020-02414-x
|View full text |Cite
|
Sign up to set email alerts
|

Inulin supplementation ameliorates hyperuricemia and modulates gut microbiota in Uox-knockout mice

Abstract: Purpose Inulin is a type of fermentable dietary fiber, which is non-digestible, and can improve metabolic function by modulating intestinal microbiota. This study aimed to evaluate the role of inulin in hyperuricemia and microbial composition of the gut microbiota in a mouse model of hyperuricemia established through knockout of Uox (urate oxidase) gene. Methods KO (Uox-knockout) and WT (wild-type) mice were given inulin or saline by gavage for 7 weeks. The effect of inulin to combat hyperuricemia was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(61 citation statements)
references
References 62 publications
(75 reference statements)
6
55
0
Order By: Relevance
“…In this study, the abundance of the genus [Ruminococcus] and the genus [Eubacterium] in the population of the AH was very low. At present, the genus Ruminococcus and the genus Eubacterium are mentioned in the population of AH and the population of gout populations, which are similar to the results of this study [ 8 ]. In this study, the reduced bacteria in the AH population also had unidentified and unclassified bacteria with low abundance, such as unclassified_Enterobacteriaceae, unidentified_Ente-robacteriaceae, unidentified _ Lactobacillales , and unclassified_Enterococcaceae .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, the abundance of the genus [Ruminococcus] and the genus [Eubacterium] in the population of the AH was very low. At present, the genus Ruminococcus and the genus Eubacterium are mentioned in the population of AH and the population of gout populations, which are similar to the results of this study [ 8 ]. In this study, the reduced bacteria in the AH population also had unidentified and unclassified bacteria with low abundance, such as unclassified_Enterobacteriaceae, unidentified_Ente-robacteriaceae, unidentified _ Lactobacillales , and unclassified_Enterococcaceae .…”
Section: Discussionsupporting
confidence: 88%
“…For example, common dietary components can be metabolized by the gut microbiota and produce metabolites that regulate host metabolism (such as dietary choline and trimethylamine). Some of these metabolites can have beneficial or harmful effects on the host [ 8 ]. Therefore, the study of the intestinal flora in patients with AH is a significant breakthrough in the study of disease pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, approximately onethird of SU is excreted through intestinal uricolysis (41), indicating that gut microbiota may play an important role in metabolization of SU (e.g., Lactobacillus gasseri strains have the ability to decrease intestinal absorption of purines) (42). Studies have shown that Coprococcus may have beneficial effects through the production of short-chain fatty acids (SCFAs), the vital metabolites for the maintenance of intestinal homeostasis (43,44). For example, studies have demonstrated that 2 SCFAs (propionate and butyrate) provide ATP to the cells of the intestinal wall to promote UA excretion (45).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperuricemia affected the composition and metabolites of the gut microbiota, especially short chain fatty acid (SCFA). Guo et al revealed the SCFA reduced in hyperuricemic mice [ 12 ]. However, few studies clarified the mechanism between the gut microbiota and hyperuricemia.…”
Section: Introductionmentioning
confidence: 99%